Advanced Q-MAC: Optimal Resource Allocating for Dynamic Application in Mobile Cloud Computing Using QoS with Cache Memory - Tara Phani Surya Kiran, K; V V Satyanarayana, K; Yellamma, P (International Journal of Engineering and Technology, 2018)
In the current era of technological advancement, mobile smart devices are being used extensively. As a result the requirements of these devices are also growing. With the help of Mobile Cloud Computing, these devices are able to communicate directly with the cloud and perform complex tasks which used to be very farfetched in the past. In such a scenario, the movement of mobile devices is the major research area. The challenge of maintaining a study link between these devices and the network is under extensive study. In this paper we propose a Advanced Q-MAC architecture for resource allocation of mobile devices. The proposed method improves the QoS of the system and higher efficiency and reliability. Experimental results show that the proposed method performs data offload better that the existing methods and has better results in terms of efficiency and process time.Â Â